Improving the corrosion resistance and osteogenic differentiation of ZK60 magnesium alloys by hydroxyapatite/graphene/graphene oxide composite coating. Issue 11 (1st June 2022) - Li, Qite; Yan, Yingzhu; Gao, Hong
Abstract: Magnesium (Mg) alloys have better biocompatibility and biodegradability than conventional biomedical metal materials, but their corrosion resistance is poor, which limits their application in bone repair materials. In this study, ZK60 Mg alloys were fabricated with hydroxyapatite (HA) and hydroxyapatite/graphene/graphene oxide (HA/G/GO) composite coatings through the hydrothermal method. Results showed that the HA coating prepared in treatment solutions of pH = 9 had the highest corrosion resistance, which was 9.77 times higher than that of ZK60. In the HA/G/GO composite coatings, GO made the HA crystals cluster into flower clusters closely, while G changed the growth orientation of the HA crystals. Moreover, the HA/G/GO composite coatings improved the corrosion resistance of the Mg alloys, and promoted the osteogenic differentiation of mesenchymal stem cells (MSCs). The corrosion resistance of the HA/3G/2GO composite coating was 28.53 times higher than that of ZK60. And HA/3G/2GO displayed the highest osteogenic differentiation among the coatings, and the order was HA/3G/2GO > HA/05GO > HA > ZK60 Mg alloy. The findings in this study can virtually expand the application of Mg alloys in bone repair materials, thus increasing the practical usage of Mg alloys in clinical applications.